I-Radicals, Their Lattices, and Some Classes of Rings - Gorbachuk, E. L.; Maturin, Yu. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We describe some I-radicals in the categories of modules over semilocal rings. We give a characterization of rings over which the set of I-radicals coincides with the set of hereditary idempotent radicals. We prove that the lattices of I-radicals in the categories of modules over Morita-equivalent rings are isomorphic.